Pengaruh Promosi Media Sosial Tiktok Dan Kualitas Produk Terhadap Penjualan Online Shop PT Sanita Sukses Mandiri - Indra Maulana; Budi Syamtoro (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The main objective of this study is to determine and analyze the influence of promotion through Tiktok social media and product quality on Online Shop sales at PT. Sanita Sukses Mandiri. This study aims to measure the extent to which these two variables contribute to increasing sales quantitatively. The research method used is quantitative, with data collection techniques employing questionnaires. Sampling was conducted using non-probability sampling with purposive sampling techniques, involving 100 respondents selected based on specific criteria. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of the t-test for the Tiktok Social media Promotion variable (X1) showed a calculated t-value of 1.90 and significance of 0.001. Since the calculated t-value is smaller than the table t-value (1.90 > 1.66) and the significance is less than 5% (0.050), Ha is accepted and H0 is rejected. It can be stated that Tiktok Social media Promotion (X1) has a significant effect on Online Shop Sales (Y). Based on the results of the t-test calculation for Product Quality (X2) with a calculated t-value of 11.898 and a significance level of 0.001. Since the calculated t-value is greater than the t-table value (11.898 > 1.66) and the significance level is less than 5% (0.050), the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It can be stated that Product Quality (X2) has a significant effect on Online Shop Sales (Y). Based on the above results, the ANOVA test yielded a calculated F value of 325.513, while the table F value (α 0.05) for n = 98 is 3.090. Therefore, F calculated > F table (α 0.05) or 325.513 > 3.090, with a significance level of 0.001 because 0.001 < 0.05, it can be said that Tiktok Social media Promotion (X1), Product Quality (X2), and together influence Online Shop Sales (Y). Based on the Model Summary table, which yields an R-Square value of 0.870, this indicates that 87% of the variables Tiktok Social media Promotion (X1) and Product Quality (X2) have a simultaneous (joint) effect on the Online Shop Sales (Y) variable, while the remaining 13% is influenced by other factors not investigated in this study.